A SEMIOTIC ANALYSIS ON MOVIE POSTERS OF HARRY POTTER AND THE DEATHLY HALLOWS - BURTY, ANNISA DHANIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Burty, Annisa Dhania. 2013., A Semiotic Analysis on Movie Posters of Harry Potter and the Deathly Hallows. Study Program of English, Universitas Brawijaya. Supervisor: Iis Nur Rodliyah; Co-supervisor: Emy Sudarwati  Movie poster has a commercial purpose as medium to advertise a movie. It delivers what the movie is all about. In this study, the writer chooses the movie poster of Harry Potter and the Deathly Hallowsas the object to be analyzed using semiotic study. This sequel is divided into two parts. There are two posters that were analyzed in this study. Each element used in a movie poster carries its own meaning. Therefore, the aim of this study is to find out the interpretation of the semiotic signs used on the movie posters of Harry Potter and the Deathly Hallows.This study uses qualitative approach in term of document or content analysis because it focuses on identifying the signs found in movie poster of Harry Potter and the Deathly Hallows. This study applied the theory of connotative meaning proposed by Chandler (2002).This study reveals that the function of the sign in each movie poster is to illustrate and guide the audience about the story of the film. The connotation is made based on the relation of the movie poster and the story along the movies. The date of the release of the film stands out, it is very important for advertisement purposes that the audience can know when they will be able to see the film.The writer suggests the next researchers can cover the limitations of this study by taking further research.  The next researcher can also apply semiotic study in other visual communication media, for example art photography, banner, and printed commercial.